Epidemiological analysis of tuberculosis cases in the Tucuruí – PA Lake Integration Region (Research, Society and Development, 2021)
This study aimed to analyze the epidemiological profile of tuberculosis (TB) in the Tucuruí Lake Integration Region (RILT), state of Pará, during the period from 2017 to 2020. This is a descriptive observational epidemiological study, of the ecological type, and quantitative approach conducted through a survey of secondary data relating to cases of TB reported in the RILT to the Information System of Notifiable Diseases. The TB notifications of the seven municipalities that make up the RILT (Breu Branco, Goianésia do Pará, Itupiranga, Jacundá, Nova Ipixuna, Novo Repartimento and Tucuruí), during the years 2017 to 2020, were included, and the notifications from outside the cited region and the analyzed period were excluded. The results revealed that, during the studied period, 482 cases of the disease were notified in the region. Moreover, an increase in the number of TB notifications in the last three years was observed. Regarding those affected by the disease, there was a prevalence of the population with low education, age range of 15 to 24 years, male gender, and pulmonary clinical form. It was concluded that the RILT presented a large number of TB cases during the analyzed period, revealing that the disease represents a serious public health problem in the region. Thus, epidemiological surveillance and health promotion actions should be implemented in the RILT in order to contribute to the reduction and control of TB cases.